Marine research and eco tourism centre: exploring notions of marine conservation, eco tourism, a social and educational intersect within the current temporal context - Dien, Ebrahim (University of the Free State, 2022)
Small rural coastal towns have unique shared experiences between humans and marine life The research question is How can a traditional Regional Coastal Vernacular form the social and educational Intersect, between industry (local fisherman and community) and oceanic life forms ( to support eco tourism in Struisbaai in the Overberg District Active. Active research in coastal Marine Protected Areas ( in the district is challenged with a lack of facilities to support the daily operations required for marine research, rehabilitation, and data collection. Traditional regional coastal (fig 01 industrial vernacular, study buildings and site context were investigated and synthesized to develop a symbiotic relationship into an architectural form to accommodate a Marine Research and Eco tourism Centre. Feedback from Marine Research experts and the fisherman community together with precedent study buildings established an interactive relevant symbiotic design. This dissertation provides solutions to address the marine conservation and eco tourism into a social and educational intersect to promote social cohesion and conservation in similar rural coastal communities.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2022